Willingness To Pay Organic Agricultural Products: Contingent Valuation Methods Approach - sucihatiningsih dwp; Dhea Rizky Amelia; Bayu Rizky Pratama; Fauzul Adzim (Economics Development Analysis Journal, 2022)
The objective of this study is to analyze the value of Willingness to Pay (WTP) of eco-friendly agricultural products and the factors that influence it. The analytical method used was the contingent valuation method (CVM) and logistic regression analysis. The results show that the total number of WTP in West Java is IDR 620,000, meaning that there will be an additional value of eco-friendly agricultural products by 620,000 for each sale. Then, the total number of WTP in Central Java is IDR 580,000 and then the total number of WTP in East Java is IDR 532,000. Based on the results of the logistic regression estimation, it shows that the variables that have a significant effect on the willingness to pay for eco-friendly agricultural products in West Java include gender, education, marital status, number of family dependents, income, and concern for the environment. Based on the results of the logistic regression estimation, it shows that the variables that have a significant effect on the willingness to pay for eco-friendly agricultural products in Central Java include age, education, number of family dependents, income, and price. Based on the results of the logistic regression estimation, it shows that the variables that have a significant effect on the willingness to pay for eco-friendly agricultural products in East Java include gender, education, marital status, number of family dependents, price, and concern for the environment.